Heavy metals concentrations in cultivated mushroom species - Ivan Širić; Valentino Držaić; Bojana Božac; Zvonimir Matijević (Journal of Central European Agriculture, 2019)
The aim of this paper was to determine the concentration of heavy metals in three commercial mushroom species: Agaricus bisporus Imbach, Pleurotus ostreatus (Jacq. ex Fr.) P.Kumm. and Lentinula edodes (Berk.) Pegler in Croatia and calculate the estimation of toxic metals inputs and contribution to toxicological values. Twenty samples of each mushroom species were selected randomly. Heavy metal analysis were carried out on an optical emission spectrophotometer with inductively coupled plasma - ICP-OES. Mercury concentration was determined on the mercury analyzer AMA-254 by direct combustion of samples in a rich oxygen atmosphere. Statistical analysis of results was carried out using software package SAS V9. The highest average concentration of iron (60.04 mg*kg-1), zinc (53.64 mg*kg-1), copper (7.06 mg*kg-1) and mercury (2.27 μg*kg-1) was determined in Agaricus bisporus. Significantly (P<0.05) higher average lead concentration (21.17 μg*kg-1) and arsenic (143.20 μg*kg-1) was determined in Pleurotus ostreatus species, while significantly higher (P<0.05) average cadmium concentration of 133.67 μg*kg-1 has been established in Lentinula edodes. The largest contribution to PTWI - temporary tolerable weekly input was determined for cadmium in the amount of 19.12% in Lentinula edodes. The stated value as well as the other established by this study does not represent a toxicological risk in case of a larger weekly consumption of the analyzed mushroom species.